The Role of T-Cadherin (CDH13) in Treatment Options with Garcinol in Melanoma - Stäbler, Sebastian; Hoechst, Sebastian; Thongmao, Aranya; Schneider, Nadja; Boßerhoff, Anja Katrin; Kuphal, Silke (Cancers, 2024)
Targeted therapies with chemotherapeutic agents and immunotherapy with checkpoint inhibitors are among the systemic therapies recommended in the guidelines for clinicians to treat melanoma. Although there have been constant improvements in the treatment of melanoma, resistance to the established therapies continues to occur. Therefore, the purpose of this study was to explore the function of garcinol with regards to specific cancer properties such as proliferation and apoptosis. Garcinol, a natural compound isolated from the plant also known as mangosteen (Garcinia mangostana), is a newly discovered option for cancer treatment. Numerous pharmaceutical substances are derived from plants. For example, the derivates of camptothecin, extracted from the bark of the Chinese tree of happiness (Camptotheca acuminate), or paclitaxel, extracted from the bark of the Western yew tree (Taxus brevifolia), are used as anti-cancer drugs. Here, we show that garcinol reduced proliferation and induced apoptosis in melanoma cell lines. In addition, we found that those cells that are positive for the expression of the cell–cell adhesion molecule T-cadherin (CDH13) respond more sensitively to treatment with garcinol. After knock-down experiments with an siRNA pool against T-cadherin, the sensitivity to garcinol decreased and proliferation and anti-apoptotic behavior of the cells was restored. We conclude that patients who are T-cadherin-positive could especially benefit from a therapy with garcinol.
CRIS-Team Scopus Importer:2024-06-07
Keywords: CDH13; garcinol; malignant melanoma; T-cadherin